1987
DOI: 10.1159/000215562
|View full text |Cite
|
Sign up to set email alerts
|

<i>Corynebacterium parvu</i><i>m</i>, but not BCG, Induces Elevations in Plasma Proteinase Activity Similar to Those Observed in Tumor-Bearing Mice

Abstract: Intraperitoneal administration of Corynebacterium parvum to BALB/c, C57B1/6 or C3H/HeJ mice lead to the induction of elevated levels of neutral proteinase activity (125I-caseinolytic activity) similar to those observed previously in animals bearing the BCL1 leukemia or the B16-F10 melanoma. Enhanced activity reached a peak at 7–14 days postin-jection of the C. parvum and then gradually returned to normal levels by 20–25 days postin-jection. Increased plasma proteinase activity could be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The cells were grown in vitro, washed three times with medium (RPMI-1640, Flow Laboratories), and then 10s cells were injected into a subcutaneous site on the flank. The pyridine extract residue of C. parvum (CP-PER) was obtained from RIBI Immuno Chemicals (Hamilton, Mont., USA) and was the same lot of material used previously [13,15]. The material was resuspended in sterile phosphate-buffered saline (PBS; pH 7.4) immediately prior to use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were grown in vitro, washed three times with medium (RPMI-1640, Flow Laboratories), and then 10s cells were injected into a subcutaneous site on the flank. The pyridine extract residue of C. parvum (CP-PER) was obtained from RIBI Immuno Chemicals (Hamilton, Mont., USA) and was the same lot of material used previously [13,15]. The material was resuspended in sterile phosphate-buffered saline (PBS; pH 7.4) immediately prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The material was resuspended in sterile phosphate-buffered saline (PBS; pH 7.4) immediately prior to use. Animals received an intraperitoneal injection of 2.5 mg CP-PER, a dose previously demonstrated to yield maxi mal disruption of plasma proteinase homeostasis [15].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can elevate the immune function via multifaceted actions, including activating macrophages, regulating T cell immune responses and promoting haematopoietic stem cells to differentiate into monocytes (Thatcher et al, 1977;Rossol et al, 1990;Matsui et al, 1997). Its therapeutic effect is comparable in some respects to BCG in mice and human (Lau et al, 1986;Hart, 1987;Lipton et al, 1991). However, many investigations have demonstrated that CP-treated mice could develop splenic intumescences and intrahepatic granulomas (Riveros-Moreno et al, 1979;Tsuji et al, 1999).…”
Section: Introductionmentioning
confidence: 98%